Intellectual property rights protection in higher education institutions of Ukraine: specifics and problems - Kulakovskyi, O.; Brovdii, A. (Problems of Engineer-Pedagogical Education, 2020)
The article deals with the peculiarities of legal relations of intellectual property protection. The subject, content and objects of intellectual property have been established. Types of legal relationships of protection of intellectual property rights in higher education in Ukraine are generalized. Attention is focused on the protection of the copyright of such legal relationships. It is stated that the type and form of intellectual property objects depend on the directions in which relevant structural units are conducting research, as well as the specialties in which students are trained in these educational institutions. It is proved that the lack of a clear understanding of the concept of originality applied to such objects of copyright as part of a work in the form of sentences, phrases, etc. It complicates the participants’understanding of the copyright protection and determination of the way of protection of the infringed intellectual property rights, including plagiarism. This is due primarily to legislative changes to ensure the quality of education and the introduction of the concept of "academic plagiarism" which, although not directly, but indirectly affect issues of copyright. In order to determine the limits of liability for copyright infringement, a comparison of the terms "academic plagiarism" and plagiarism was made. It is established that the problem of copyright infringement is urgent not only in Ukraine but also in other countries of the world. It is substantiated that lack of knowledge about intellectual property rights violations and academic integrity violations is one of the contributing factors to violations in this area. It is necessary to develop competences in the field of intellectual property and in other areas closely related to (academic integrity) students of higher education institutions, scientific, pedagogical, scientific and pedagogical workers. A survey was conducted among students of pedagogical and pharmaceutical specialties in order to obtain information about the desired form of knowledge in this field. The most preferred forms of knowledge acquisition in this field are lectures and practical classes.